pendidikan, belajar, covid IMPLEMENTASI PENDEKATAN ANDRAGOGI DI PKBM BUDI UTOMO : Indonesia - Elisabeth Manurung; Jubaidah Hasibuan; Monika Agustina Hutabarat; Naser Maulidina Fitra Suci; Rotua Mei Yohana Simanjuntak; Sonya Zefanya Siburian; Wilma Winanda Putri Sirait (JPUS: Jurnal Pendidikan Untuk Semua, 2025)
This study aims to find out related to the implementation of the andragogy approach at PKBM Budi Utomo. This study uses an approach with a descriptive method where the subject in this study is Mrs. Jumiah as the owner of PKBM Budi Utomo. Data collection is done directly with the methods of observation, interviews, and documentation. The research found is 1) an adragogic approach to learning at PKBM Budi Utomo with 4 indicators, namely security, affection, new experiences, and recognition, 2) Adult learning styles at PKBM Budi Utomo, namely a free learning style where students can present whenever they want, 3) The assumption of adult learning at PKBM Budi Utomo which consists of 7 things, namely preparing a conducive learning climate, creating a joint planning mechanism, determining learning needs, formulating special goals, designing learning experience patterns, implementing programs (carrying out activities). learning), developing learning outcomes and redefining learning needs. Researchers also found several problems that exist in Budi Utomo's PKBM, namely: 1) Students rarely take part in learning because they are busy with their respective jobs, 2) lack of motivation of students in participating in learning, 3) Lack of understanding of students in receiving explanations of learning material from tutors, and 4) the difficulty of carrying out bold learning due to not having a cellphone or being exposed to network problems